Evaluation of the shape memory behavior of a poly(cyclooctene) based nanocomposite device. Issue 3 (11th April 2017) - Dorigato, A.; Pegoretti, A.
Abstract : The objective of the present work is to investigate the electro‐activated shape memory behavior of a polycyclooctene (PCO) based nanocomposite device. At this aim, carbon black (CB) and exfoliated graphite nanoplatelets (xGnP) were melt compounded with a PCO matrix crosslinked with a dicumylperoxide content of 2 wt% and a total filler amount of 4 wt%. Electrical resistivity measurements on bulk materials evidenced a noticeable decrease of the electrical resistivity upon CB addition, while no synergistic effects were detected mixing CB and xGnP. Nanocomposite with a CB amount of 4 wt% revealed also a noticeable heating capability through Joule effect for voltage levels higher than 100 V. The subsequent characterization of an electro active shape memory device based on this composition demonstrated how it is possible to prepare a shape memory nanocomposite material able to completely recover its original shape after 100 s with a voltage of 90 V. The retention of the shape memory behavior after several (50) programming cycles was also demonstrated. POLYM. ENG. SCI., 58:430–437, 2018. © 2017 Society of Plastics Engineers